2018
DOI: 10.33854/jbdjbd.45
|View full text |Cite
|
Sign up to set email alerts
|

PERBANDINGAN PROSES PENYEMBUHAN TULANG ANTARA IMPLANTASI HIDROKSIAPATIT NANOKRISTALIN DAN HIDROKSIAPATIT MIKROKRISTALIN (Kajian pada tulang tibia kelinci

Abstract: Latar belakang. Salah satu bahan alloplastik yang berkembang pesat saat ini yaitu hidroksiapatit (HA) sintetik. Hidroksiapatit sintetik konvensional yang banyak digunakan saat ini yaitu hidroksiapatit mikrokristalin dimana struktrur kristalnya berada dalam kisaran mikrometer. Beberapa dekade terakhir bentuk nanokristalin dari hidroksiapatit (10-100 nm) mendapat perhatian dari banyak peneliti terutama mengenai sifat fisik, mekanik, kimia dan biologisnya karena hidroksiapatit nanokristalin ini lebih menyerupai b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Compared to nano-HA, microcrystalline HA has a low level of solubility, so it is not easily absorbed. Based on a study conducted by Pascawinata et al 14 , when implanted in bone defects, this HA can be well covered and even partially replaced by new bone. However, the resorption process takes a long time and is still seen in the experimental animal after nine months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to nano-HA, microcrystalline HA has a low level of solubility, so it is not easily absorbed. Based on a study conducted by Pascawinata et al 14 , when implanted in bone defects, this HA can be well covered and even partially replaced by new bone. However, the resorption process takes a long time and is still seen in the experimental animal after nine months.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts and osteoclasts that adhere more to the nanocrystalline HA accelerate the healing process of bone injuries. 14 As well as the particle size, tooth graft powder also contains some beneficial components for cell proliferation. Ninety percent of the organic components of teeth are type I collagen and contain growth factors such as IGF-II, BMP2, and bone-like TGF-beta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoblasts will secrete TGF-β1 during the proliferation stage, and then TGF-β1 will again stimulate osteoblasts through the autocrine effect [11]. Level of ALP in the treatment group was higher than in the control group because hydroxyapatite has good quality of osteoconduction, osteoinduction, and osteointegration [28]. Hydroxyapatite gel in the socket will stimulate the release of cytokines from endothelial cells through inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of osteoblasts and osteoclasts is known to occur more in nanocrystalline HA than conventional HA [35]. Pascawinata et al (2013) study showed more and faster bone healing in defects implanted using nanocrystalline HA than conventional HA and defects left blank [36]. The advantages of nanocrystalline HA as bone graft material are its closer contact with the surrounding tissue, its faster absorption, and the high number of molecules on its surface.…”
Section: Ha Nanocrystallinementioning
confidence: 97%